Expression of matrix metalloproteinase-2 and metalloproteinase-9 in the skin of dogs with visceral leishmaniasis - Jacintho, Ana Paula Prudente; Melo, Guilherme D.; Machado, Gisele F. [UNESP]; Bertolo, Paulo Henrique Leal [UNESP]; Moreira, Pamela Rodrigues Reina [UNESP]; Momo, Claudia; Souza, Thiago A. [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP] (Springer Nature, 2018)
The skin is the first organ to be infected by the parasite in canine visceral leishmaniasis. The enzyme matrix metalloproteinase (MMP) acts towards degradation of the extracellular matrix (ECM) and modulation of the inflammatory response against many kinds of injuries. The aims of this study were to evaluate the expression of MMP-2 and MMP-9 through immunohistochemistry and zymography on the skin (muzzle, ears, and abdomen) of dogs that were naturally infected by Leishmania spp. and to compare these results with immunodetection of the parasite and with alterations to the dermal ECM. Picrosirius red staining was used to differentiate collagen types I and III in three regions of the skin. The parasite load, intensity of inflammation, and production of MMP-2 (latent) and MMP-9 (active and latent) were higher in the ear and muzzle regions. MMP-9 (active) predominated in the infected group of dogs and its production was significantly different to that of the control group. Macrophages, lymphocytes, and plasma cells predominated in the dermal inflammation and formed granulomas in association with degradation of mature collagen (type I) and with discrete deposition of young collagen (type III). This dermal change was more pronounced in dogs with high parasite load in the skin. Therefore, it was concluded that the greater parasite load and intensity of inflammation in the skin led consequently to increased degradation of mature collagen, caused by increased production of MMPs, particularly active MMP-9, in dogs with visceral leishmaniasis. This host response profile possibly favors systemic dissemination of the parasite.
Keywords: Dog; Gelatinases A and B; Immunohistochemistry; Leishmania infantum; Skin; Zymography